Study on the taste active compounds in Douchi using metabolomics method. (30th June 2023) - Guo, Weidan; Zhang, Yu; Long, Zhao; Fu, Xiangjin; Ren, Kangzi
Graphical abstract: Highlights: The umami was significantly negative correlating with sourness in Douchi. The richness was positively correlated with astrigent and after-astrigent in Douchi. The arginine biosynthesis and glutamate metabolism pathway were enriched in Douchi. Other than glutamate, the succinic acid play a more key role for umami in Douchi. The lactic acid was the key sour metabolite in LY, and YJ, as the l -malic acid in YC. Abstract: Douchi is a traditional famous seasoning in China. This study adopted electronic tongue and metabolomics to analyze the taste characteristics and taste active compounds of 12 samples from three most famous types of Douchi (Liuyang Douchi, Yangjiang Douchi, Yongchuan Douchi). Thirty-six differential metabolites mainly enriched from the arginine biosynthesis were identified among these Douchis. Umami and bitterness are considered as two taste that bring positive and negative perceptions for Douchi. The succinic acid was found to be responsible for the umami in LY, YJ and YC Douchi, with the TAVs of 2054, 643, 174, respectively, rather than the glutamic acid and aspartic acid. The leucine was identified as the main metabolite for bitterness, with the TAVs of 9, 9, 7 respectively. KEGG enrichment analysis found that the umami, sourness and saltiness might be related to alanine, aspartate and glutamate metabolism and the bitterness might be related to aminoacyl-tRNA biosynthesis pathway.